Dynamic response mechanism of layered coatings under impacts: Insights from the perspective of stress wave - Mai Yang; Rong Tu; Mingquan Jiang; Wei Liu; Tenghua Gao; Baifeng Ji; Jun Li; Song Zhang; Lianmeng Zhang (Materials & Design)
Precision machining operations often lead to the failure of protective coatings on cutting tools due to common issues such as cracking, delamination, and peeling from cyclic impacts. While material selection and structural design are crucial for enhancing impact resistance, they primarily focus on static performance with limited consideration from the dynamic sights. This paper presents a novel dynamic design method for coatings, viewed through the lens of stress waves. We investigate the propagation behavior of stress waves in TaN/TiN and CrN/TiN coatings with layered structures. Our findings indicate that the attenuation of stress waves is dominated by the physical properties on both sides of the interface and the stride length. For interfaces with similar physical properties, the attenuation of stress waves is insensitive to the stride length, while for interfaces with different physical properties, the attenuation is regulated by the ratio of single-layer thickness to the full width at half maximum of the stress wave. These insights offer a strategy for extending the life of coatings and improving process safety under dynamic shocks.